Bibliometric Analysis of Agroforestry Research in Tropical Countries in Publications from 2010 to 2024 - Loso Judijanto (West Science Agro, 2026)
This study aims to map the development of agroforestry research in tropical countries during the period 2010–2024 using a bibliometric approach. Agroforestry has increasingly been recognized as a multifunctional land-use system capable of integrating climate mitigation, biodiversity conservation, and rural livelihood improvement. However, the rapid growth of publications has made it difficult to comprehensively understand research trends, collaboration structures, and thematic evolution within this field. To address this gap, this study analyzes publications indexed in the Scopus database and employs VOSviewer to visualize co-authorship networks, institutional collaborations, country partnerships, keyword co-occurrence patterns, overlay visualization, and density mapping.  The results indicate a significant increase in research output over the last decade, with strong international collaboration networks linking developed countries and tropical regions. The United States, United Kingdom, Germany, and India emerge as central contributors, while tropical countries such as Indonesia, Brazil, Kenya, and Ethiopia are increasingly active in global research partnerships. Thematic analysis reveals that agroforestry research is strongly centered on climate change, biodiversity, ecosystem services, and food security. Overlay visualization shows a temporal shift from earlier conservation-focused studies toward more integrated themes related to carbon sequestration, climate resilience, and smallholder livelihoods.